ROLE OF DEFLAZACORT AS AN ADJUVANT TO TAMSULOSIN IN ENHANCING EXPULSION OF MIDDLE AND LOWER URETERIC CALCULI: A PROSPECTIVE COMPARATIVE STUDY - SINGH, PIYUSH; SINGH, SHIKHA (International Journal of Current Pharmaceutical Research, 2026)
Objective: Ureteric calculi constitute a significant proportion of urolithiasis cases and commonly present with acute colicky pain, urinary symptoms, and recurrent morbidity. Medical expulsive therapy (MET) using α-blockers such as tamsulosin is widely practiced; however, adjunctive corticosteroids may further facilitate stone passage by reducing ureteric edema and inflammation. This study evaluates the effectiveness of combining deflazacort with tamsulosin versus tamsulosin monotherapy in enhancing expulsion of middle and lower ureteric stones. Methods: This prospective comparative study was conducted at People’s Hospital, Bhopal, from November 2022 to March 2024. A total of 170 eligible patients with unilateral middle or lower ureteric calculi (4–8 mm) were randomized into two groups: group A received tamsulosin 0.4 mg daily plus deflazacort (6 mg twice daily for 2 w, tapered to 6 mg once daily for 2 more weeks), and group B received tamsulosin monotherapy. Patients were followed for up to 4 w, with serial assessment of stone expulsion, analgesic requirement, and adverse events. Statistical analyses were performed using SPSS v26, with p<0.05 considered significant. Results: Stone expulsion at 3 w was significantly higher in Group A compared to Group B (23.5% vs. 7.1%; p<0.01). By 4 w, expulsion rates further increased to 88.2% versus 52.9%, respectively (p<0.01). The overall treatment success rate was markedly superior in Group A (90.4%) compared to Group B (56.1%; p<0.01). Analgesic requirements were significantly lower with combination therapy (mean 4.59 vs. 6.38 doses; p<0.01). Adverse events were mild and comparable between groups. Conclusion: Deflazacort as an adjunct to tamsulosin significantly enhances stone expulsion rates, accelerates clearance, and reduces analgesic use without increasing adverse effects. Combined MET is a safe and effective strategy for middle and lower ureteric calculi.